2010
DOI: 10.3136/fstr.16.215
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Free and Bound Phenolic Acids, and Evaluation of Antioxidant Activities and Total Polyphenolic Contents in Selected Pearled Barley

Abstract: The content of insoluble bound phenolic acids in pearled barley was determined by an analytical system consisting of alkaline hydrolysis extraction, high-performance liquid chromatographic separation and electrochemical detection. Insoluble bound phenolic acids in five pearled cultivars and fifteen breeding lines of barley comprised ferulic acid (4.3-34.2 mg/100 g dry matter), sinapic acid (0.025-0.445 mg/100 g), caffeic acid (0.002-0.016 mg/100 g). Soluble free polyphenols comprised procyanidins (12.2-80.3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Several reports have reinforced the case for whole grains as health-promoting components in the diet. [1][2][3] Recently, barley (Hordeum vulgare L.) has gained renewed interest as an ingredient for the production of functional foods and beverages. [4][5][6] Barley is a widely consumed cereal over the world, mainly as animal feed and malt, which is a raw material for the beer and spirit industry.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several reports have reinforced the case for whole grains as health-promoting components in the diet. [1][2][3] Recently, barley (Hordeum vulgare L.) has gained renewed interest as an ingredient for the production of functional foods and beverages. [4][5][6] Barley is a widely consumed cereal over the world, mainly as animal feed and malt, which is a raw material for the beer and spirit industry.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Barley is a widely consumed cereal over the world, mainly as animal feed and malt, which is a raw material for the beer and spirit industry. [3,4,7] Both barley grain and malt contain high levels of antioxidative phenolic compounds. [2][3][4]8] Gupta et al [9] reported that about 80% of phenolic compounds of beer are derived from barley malt and the remaining come from hop, indicating the importance of these compounds during mashing and brewing.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations